Pelindungan Hukum Ketenagakerjaan Atas Jaminan Keberlangsungan Bekerja terhadap Pekerja dengan Perjanjian Kerja Waktu Tertentu pada Perusahaan Alih Daya Ditinjau dari Teori Keadilan - Kartika, Andri; Suherman, Ade Maman; Setiady, Tri (Universitas Batanghari Jambi, 2025)
Regulations governing worker rights safeguarding are enacted via Outsourcing as specified in Government Regulation Number 35 of 2021, a response to the worldwide economic climate. Outsourcing serves as a strategy by the government to tackle global economic challenges, enabling business owners to preserve the viability and continuity of their enterprises during the economic downturns experienced both within Indonesia and globally as a result of the Covid-19 pandemic. In practice, the implementation of internship programs often experiences various problems. Among them, Interns are often positioned as workers without getting the rights they deserve, such as decent wages, insurance, or career advancement opportunities, even internship participants have the potential to become or replace Outsourcing and/or Outsourcing workers. So that the use of Outsourcing is affected by termination of employment. The purpose of this study is to examinelegal protection in Government Regulation Number 35 of 2021 regarding the guarantee of the continuity of work for Fixed Time Work Agreement (PKWT) workers in outsourcing companies who are laid off, reviewed from the theory of justice and to examinethe occurrence of Termination of Employment of Fixed Time Work Agreement (PKWT) workers at PT. X as an outsourcing company. The methodology employed in this study is characterized by normative legal research, focusing on the examination of secondary or primary Legal Protection materials such as theories, legal concepts, principles, and regulations. The gathering of data was executed through bibliographic research and empirical research, deriving from secondary sources like interviews and observations. Subsequently, this data was subjected to qualitative analysis to derive the anticipated outcomes of the research. The examination of Legal Protection within Government Regulation Number 35 of 2021 concerning the assurance of work continuity for PKWT workers in Outsourcing firms, interpreted through the lens of justice theory, reveals that multiple PKWT Workers at PT. X were dismissed as their tasks were assigned to interns participating in a local internship scheme facilitated by the Employing Company for the Outsourcing Company. Observing the events that transpired, the researcher concludes that the safeguarding of job continuity stipulated in Government Regulation Number 35 of 2021 does not meet the criteria of fairness for PKWT Workers employed by the Outsourcing company.